Wikipedia in the information-seeking routine : reader usage and opinions of Wikipedia. - Lim, Ying Ling. (2009)
This study explores how readers utilise Wikipedia to seek information, and their perceptions of the website. Six Wikipedia users were invited to keep a journal, tracking their Wikipedia usage. Their journal entries were then analysed to gain insights into the users’ usage habits, opinions and relationships with Wikipedia.